Housing development and consumer protection: a study on the issue of late delivery of vacant possession from the consumer perspective - Amin, Naemah; Kassim, Salina; Syed Abdul Kader, Sharifah Zubaidah (2015)
A delay in completion of housing project is a common phenomenon in the housing industry in Malaysia. Buyers are often forced to accept the fact that it is 'better late than never'. Late delivery has several negative implications to the customers which actually causes financial, social and emotional problems to the house buyers. This study aims to explore consumers’ experiences with regard to the problems of late delivery in housing projects in Malaysia. In methodology, the paper conducts a survey on 406 house owners who had experienced the late delivery of the houses in the Klang Valley and Selangor areas. Findings of the study would provide the information of what are the implications of the late delivery to the consumers and analyse the adequacy of the existing legal protection to consumers of late delivery. Ultimately, the study hopes to shed light on further improvements of the policy to minimize or prevent the delay in completing the housing project as well as to protect consumer interests in the case of late delivery of vacant possession in the housing market in Malaysia.